Asian development outlook (ADO) 2021 financing a green and inclusive recovery. (Asian Development Outlook., 2021)
Growth in 2021 is forecast to be strongest in East and South Asia, and more moderate in Central and Southeast Asia and the Pacific. The main risks to the outlook are new virus outbreaks or delays in vaccine procurement and administration. Prolonged unemployment and disrupted education caused by the pandemic could have long-term consequences.